Journals 1952 - 2000 - Schlesinger, Arthur M. 1917-2007 (Penguin Press, 2007)
The distinguished political historian's journals provide an intimate history of post-war America, the writer's contributions to multiple presidential administrations, and his relationships with numerous cultural and intellectual figures
Includes index
Keywords: Schlesinger, Arthur M. / (Arthur Meier) / 1917-2007 / Diaries; Schlesinger, Arthur M <1917-2007> -- (Arthur Meier) -- Diaries; Schlesinger, Arthur M. -- 1917-2007; Historians / United States / Diaries; Alltag, Brauchtum; Geschichte; Politik; Historians -- United States -- Diaries; United States / History / 1945-; United States / Social life and customs / 1945-1970; United States / Social life and customs / 1971-; United States / Politics and government / 1945-1989; United States / Politics and government / 1989-; Verenigde Staten; USA; United States -- History -- 1945-; United States -- Politics and government -- 1945-1989; United States -- Politics and government -- 1989-; United States -- Social life and customs -- 1945-1970; United States -- Social life and customs -- 1971-; Tagebuch -- 1952-2000